2012
DOI: 10.1021/om3008234
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Nitrene Transfer as a Tool for the Synthesis of N-Substituted 1,2-Dihydro- and 1,2,3,4-Tetrahydropyridines

Abstract: The sequential reaction of two different furans and PhI=NTs produces 1,2-dihydropyridines in a quantitative manner in the presence of Tp Br3 Cu(NCMe) (Tp Br3 = hydrotris(3,4,5-tribromopyrazolyl)borate) as the catalyst under very mild conditions. The use of a furan and ethyl vinyl ether with PhI=NTs has led to the corresponding 1,2,3,4-tetrahydropyridine. ■ INTRODUCTIONThe metal-mediated catalytic transfer of nitrene (NR) groups to saturated or unsaturated substrates constitutes a useful tool in organic synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In a previous work from our laboratory we demonstrated that the copper catalyst Tp Br3 Cu(NCMe) induces the assembly of two molecules of furans and one NTs unit (from PhI=NTs) leading to the formation of 1,2‐dihydropyridines . We have now found the related transformation in which we employ one furan and one pyrrole along with PhI=NTs en route to the isolation of a 1,2‐dihydropyridine‐imine compound (Scheme ).…”
Section: Resultsmentioning
confidence: 88%
“…In a previous work from our laboratory we demonstrated that the copper catalyst Tp Br3 Cu(NCMe) induces the assembly of two molecules of furans and one NTs unit (from PhI=NTs) leading to the formation of 1,2‐dihydropyridines . We have now found the related transformation in which we employ one furan and one pyrrole along with PhI=NTs en route to the isolation of a 1,2‐dihydropyridine‐imine compound (Scheme ).…”
Section: Resultsmentioning
confidence: 88%
“…The applicability of this method to the generation of multiple 1,2-dihydropyridines and 1,2,3,4-tetrahydropyridines was later emphasized, with studies that further evaluated the scope of this reaction. 13 In that work, a two-step synthesis was proposed. In a first step, several analogues of I2 were formed by a stoichiometric nitrene transfer to the corresponding furan by the complex Tp Br3 Cu(NCMe).…”
Section: Methodsmentioning
confidence: 99%
“…The CuTp R could also catalyze aziridination using chloramine‐T in CH 3 CN to give more environmentally benign NaCl (vs. PhI) as a co‐product . Tp Br3 Cu(CH 3 CN) was also found to catalyze nitrene transfer from PhI=NTs to furans in room temperature CH 2 Cl 2 to give dihydropyridines . AgTp* or Ag(Tp *,Br ) were found to be excellent catalysts for aziridination of styrenes, 2‐alkenes, and even E,E ‐hexadien‐1‐ol in room temperature CH 2 Cl 2 using PhI=NTs as a nitrene source .…”
Section: Introductionmentioning
confidence: 99%